The Impact of Emotional Branding and Service Quality on Customer Satisfaction of Haus Indonesia - Hanifah Rani Nur’aini; Luthpiyah Juliandara; Yuni Astuti Tri Tartiani (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Indonesia's food and beverage sector recorded a 5.53% expansion in the second quarter of 2024, signaling sustained momentum. Haus Indonesia pursues innovation through Haus Keliling (Huling) mobile service, designed to raise customer satisfaction and secure the company's competitive position.Purpose: To assess if emotional branding and service quality positively influence consumer satisfaction with Haus Indonesia products.Design/methodology/approach: This quantitative descriptive study was conducted from March to July 2025 across all Haus Indonesia branches in West Java. Data were collected through a questionnaire, using purposive sampling with a sample size of 100 participants. The data were analyzed using SPSS version 29, which included validity and reliability tests, OLS assumption tests, multiple regression analysis, t-tests, F-tests, and correlation coefficients.Findings/Results: Emotional Branding (β1 = 0.461, t = 4.592, p < 0.001) and Service Quality (β2 = 0.589, t = 7.247, p < 0.001) both have a positive and significant impact on Customer Satisfaction. Together, they account for 91.8% of the variance in customer satisfaction (R² = 0.918).Conclusion: Both emotional branding and service quality are important factors influencing customer satisfaction at Haus Indonesia. Service quality has a stronger effect (β2 = 0.589) compared to emotional branding (β1 = 0.461). This suggests that while emotional engagement strategies are valuable, prioritizing operational service excellence is essential.Originality/value (State of the art): This study presents new evidence regarding the synergistic effects of emotional branding and service quality on customer satisfaction within Indonesia's rapidly expanding food and beverage industry. Focusing specifically on Haus Indonesia, it underscores the significance of emotional engagement and the overall service experience in influencing consumer satisfaction in the context of a local brand. Keywords:  customer satisfaction, emotional branding, service quality, Haus Indonesia, mobile service